Respuestas

2013-08-25T21:13:40+02:00

1) ( x - 5)² + x(x + 3) = 25
     x^2 - 10x + 25 + x^2 + 3x = 25
      2x^2 - 7x = 0
        x(2x - 7) = 0
                                             x1 = 0
                 2x - 7 = 0
                        2x = 7            x2 = 7/2           S = {0, 7/2}

2) x² - 10x + 5 = 0
          delta = (-10)^2 - 4.1.5 = 100 - 20 = 80             raiz = 4(raiz de 5)
          x = [10 - 4(raiz de 5)]/2      
                                                         x1 = 5 - 2(raiz de 5)
                                                         x2 = 5 + 2(raiz de 5)
                                          S = [5 - 2(raiz de 5)], [5 + 2(raiz de 5)]
  
                                              Menor solución: 5 - 2(raiz de 5)